Economy and Exchange in the Iron Age Kingdoms of the Southern Levant - Master, Daniel M. (Bulletin of ASOR, 2014)
Studies of the ancient world, and of the ancient Near East in particular, disagree over how to characterize the ancient economy. This paper attempts to contribute to this discussion by outlining an economic framework for the Iron Age kingdoms of the southern Levant. Three institutions—the kingdom, the market, and the trade route—provided opportunities for exchange, each according to a distinct economic rationale.